Suboptimal evolutionary novel environments promote singular altered gravity responses of transcriptome during Drosophila metamorphosis - Herranz, Raul; Larkin, Oliver J.; Hill, Richard J.A.; Lopez-Vidriero, Irene; van Loon, Jack J.W.A.; Medina, F. Javier (BioMed Central, 2013)
Background